FORMULATION OF AN ANTI-BACTERIAL CREAM FROM PLANTOXALIS CORNICULATA ANDITS EVALUATION - JOHNSON, BATHSA LIZA; ARAKAREDDY, BHANUPRAKASH; SAM, KEZIA K. (International Journal of Current Pharmaceutical Research, 2020)
Objective: Even in areas where modern medicine is available, the interest on herbal medicines and their utilization have been increasing rapidly in recent years. Plant-derived substances and herbal medicines have recently attracted the great interest towards their versatile application as medical plants are the rich source of bioactive compounds used in traditional and modern medicine. The present work is to formulate and evaluate the antibacterial cream of oxalis corniculata extract. Methods: The ethanolic extracts were prepared by using the maceration method. Results: The agrochemical potential of methanolic extract, n-hexane, chloroform, ethyl acetate,and n-butanol soluble sfractions showed excellent activites against Escherichia coli, Shigella dysenteriae, Salmonella typhi, and Bacillus subtilis. Similarly the crude n-hexane and chloroform fractions were also found to have significant activity against fungal strains including Fusarium solani, Aspergillus flexneri, and Aspergillus flavus. Conclusion: Oxalis corniculata is a common medicinal plant widely used against numerous infectious diseases. The two isolated compounds 5-hydroxy-6,7,8,4’-tetra methoxy flavone and 5,7,4’-trihydroxy-6,8-dimethoxyflavone were evaluated for antibacterial and antifungal activities. The results showed that latter compound was more active than that of the former.